Erratum: “Quantum and classical molecular dynamics for H atom scattering from graphene” (J. Chem. Phys. 159, 194102 (2023)) - Shi, Lei; Schröder, Markus; Meyer, Hans-Dieter; Peláez, Daniel; Wodtke, Alec M.; Golibrzuch, Kai; Schönemann, Anna-Maria; Kandratsenka, Alexander; Gatti, Fabien (The journal of chemical physics, 2024)
In our article,1 Fig. 12 was inadvertently mixed with other results. The correct figure should be as follows (Fig. 1).